The relationship between the typical errors in the translation of business idioms and their lexicographical treatment - Fraile Vicente, Esther (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2007)
This essay is based on the complexity involved in the translation of English business idioms into Spanish, due to the fact that these linguistic constructions are created with metaphors and based on associations of meaning that have not yet been studied sufficiently. By performing a translation experiment with my students, some conclusions are drawn regarding the difficulties inexperienced translators face and how dictionaries should cope with them. It is suggested that, most general and specialized dictionaries do not offer exact translation equivalents for idioms, but present versions that either belong to a different language level, show a lost of semantic content, have a different frequency, are archaic or erroneous. To solve these limitations, the lexicographical resources should not only include idioms as lemmas, but also offer more syntactic-semantic information with them and to structure it more systematically.